2018
DOI: 10.9775/kvfd.2017.19167
|View full text |Cite
|
Sign up to set email alerts
|

Poksvirüs İle Doğal Enfekte Koyunlarda, Bazı Akut Faz Proteinler, Biyokimyasal Parametreler ve Oksidatif Stresin Belirlenmesi

Abstract: The aim of the present study was to determine oxidative stress and acute phase response in naturally infected sheep with poxvirus. For this purpose, 20 poxvirus infected and 10 clinically healthy sheep were used in the study. In these animals, alkaline phosphatase (ALP), aspartate aminotransferase (AST) activity, haptoglobin, ceruloplasmin, urea, creatinine, albumin, iron (Fe), malondialdehyde (MDA) and reduced glutathione (GSH) concentrations were determined. The present study determined that the concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…There are also situations in which increase was detected in SOD and GPx activity with oxidants such as MDA, H 2 O 2 and decrease in CAT activity [88] . In sheep infected with sheeppox virus, an increase was found in MDA, while a decrease was found in GSH and albumin [89] . This decrease in albumin results from suppression of the antioxidative system and negative acute phase reactant due to infection.…”
Section: Oxidative Stress In Viral Infectionsmentioning
confidence: 93%
“…There are also situations in which increase was detected in SOD and GPx activity with oxidants such as MDA, H 2 O 2 and decrease in CAT activity [88] . In sheep infected with sheeppox virus, an increase was found in MDA, while a decrease was found in GSH and albumin [89] . This decrease in albumin results from suppression of the antioxidative system and negative acute phase reactant due to infection.…”
Section: Oxidative Stress In Viral Infectionsmentioning
confidence: 93%
“…19 Although there are limited studies in calves, a study conducted in calves with enzootic pneumonia reported that vitamin D concentrations were decreased in diseased animals. 4 What we do know is that vitamin D concentrations are lower in calves from birth until they are 3 months old that serum vitamin D concentrations may not increase despite vitamin supplementation during this early age, and that there is a lack in the development of immunity, making these young animals prone to lung diseases. 13 Accordingly, it has been suggested that serum vitamin D concentrations should be measured in young calves.…”
Section: Variablesmentioning
confidence: 99%
“…In addition to these physical and environmental factors, various bacteria, viruses, and other infectious agents are found alone or together in the etiology of this disease. 2 The diagnosis of enzootic pneumonia is based on clinical findings seen most often in 2-to 6-month-old calves [2][3][4] ; manifestations include cough, breathing difficulties, varying degrees of fever, and nasal discharge, which are sufficient for clinical diagnosis. Deep nasal swabs and swabs of ocular discharge are recommended for the detection of viral pathogens, whereas transtracheal aspiration and bronchoalveolar lavages are recommended for the detection of bacterial and mycoplasma pathogens.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations